Stability and sustainability assessment for the surface failure of various rock slopes excavated along the Konya-Alanya Road segment, Turkey - Ali Ferhat BAYRAM; Ahmed Ibraheem Mohamed; Arsalan Ahmed OTHMAN (Kuwait Journal of Science)
Most of the road networks in Turkey pass through the Hilly region. These roads, therefore, are constructed through inadequate blasting, accompanied by road deterioration and collapse. To date, several researchers in Turkey have not paid adequate attention to the stability (structural) analysis of road failures based on the surface orientation of the dominant discontinuity sets. This study, therefore, based on the field survey, laboratory measurements, and the use of Dips analyst software, aims to investigate the stability and sustainability of seven different sites that exhibit imminent slope failure along the Konya-Alanya road segment. The sites selected are geologically investigated and geotechnically evaluated using a scan-line survey. Several fields and laboratory measurements have also been carried out in this research. Both Slope Mass Rating and Rock Mass Rating are quantified and included with rock mass assessment of each slope site. Both the field and laboratory results are integrated together by kinematic analysis methods in Dips software to assess the potential failure of these slopes. The kinematic analysis results show that five of the seven sites are risky, thus, described as partly stable, and the other two are unstable. It also demonstrates that the common failure forms are planar, wedge, and toppling. The results have also implications for the understanding of the causal factors for slope instability, include the discontinuities presence in the rock mass, physical, environmental, and meteorological factors influencing them. In conclusion and based on the analysis, for a sustainable road and to prevent or at least to mitigate any failures on those slopes, this study concludes that urgent remedial measures for loose rocks through the construction of self-rock walls for their long-term stability are recommended.